2020
DOI: 10.3389/feduc.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

Potential Factors to Enhance Students' STEM College Learning and Career Orientation

Abstract: In this study, we highlight the importance of high school students having a college-attending and career-ready mindset in STEM fields. With this purpose, we adopted a stepwise multiple regression analysis to determine which variables are significant predictors of students' STEM college learning and career orientation. The participants were 1,105 high school students from nine randomly selected high schools across greater Houston Texas. Forty-two percent of the variance on STEM college learning and career orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The study recommended that occasional disengagement from rigorous academic engagement (unsupervised activities, gaming, and carelessness) hold the possibility of predicting and can avail actionable data for stakeholders to integrate early interventions to encouraging learners in taking up careers in STEM. Rivera and Li (2020) study randomly sampled one thousand, one hundred and five respondents to investigate significant predictors of STEM college learning and career orientation through multiple regression analysis across high schools in Houston Texas. In the study, 42% variance was revealed as STEM college learning and career orientation among six outcome predicting variables, which include STEM related activities engagement, technology/facilities, parental influence, academic experience, self-esteem and effective teacher pedagogy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study recommended that occasional disengagement from rigorous academic engagement (unsupervised activities, gaming, and carelessness) hold the possibility of predicting and can avail actionable data for stakeholders to integrate early interventions to encouraging learners in taking up careers in STEM. Rivera and Li (2020) study randomly sampled one thousand, one hundred and five respondents to investigate significant predictors of STEM college learning and career orientation through multiple regression analysis across high schools in Houston Texas. In the study, 42% variance was revealed as STEM college learning and career orientation among six outcome predicting variables, which include STEM related activities engagement, technology/facilities, parental influence, academic experience, self-esteem and effective teacher pedagogy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While there are global, national and domestic efforts to encourage students to study STEM related disciplines for over three decades, the projection in terms of expertise have been well speculated and funded to propel emerging learners (Litchtenberger & Casey, 2018;National Science Board, 2017;OECD, 2019b;Peña-Calvo et al, 2016). Governments and stakeholders have budgeted significantly to ensure the gap between demand and supply is remediated with little success on record now (Nasir et al, 2022;Rivera & Li, 2020;Tan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Within the NACP, EAC has helped to destigmatize science and STEM for many AI/AN and minority individuals, one of the commonly cited barriers to STEM [125]. Dozens of students have been mentored through the NACP partnership using the lens of EAC methodologies to understand how environmental contaminants effect human and ecosystem health.…”
Section: Discussionmentioning
confidence: 99%
“…Early and consistent exposure to science, technology, engineering, and math (STEM) leads to increased career choices in these fields. 2,3 Six predictor variables were recently identified that support STEM college learning and career orientation in high school students, including: parental involvement, STEM related activities engagement, academic experience, teacher effective pedagogy, technology/facilities, and self-esteem. 3 Of these, university professors can directly contribute to STEM-related activities engagement by acting as advisors for voluntary high school science fair projects.…”
Section: High School Regional Science Fairsmentioning
confidence: 99%
“…2,3 Six predictor variables were recently identified that support STEM college learning and career orientation in high school students, including: parental involvement, STEM related activities engagement, academic experience, teacher effective pedagogy, technology/facilities, and self-esteem. 3 Of these, university professors can directly contribute to STEM-related activities engagement by acting as advisors for voluntary high school science fair projects. High school science fairs can be competitive or non-competitive and occur at several levels.…”
Section: High School Regional Science Fairsmentioning
confidence: 99%